KORELASI TINGKAT PENGETAHUAN PASIEN DIABETES TIPE- 2 DENGAN KEPATUHAN MINUM OBAT DIABETES DI KARAWANG KULON - Lina Aliyani Mardiana; Sri Mulyanthy Tanuwidjaja; Ermi Abriyani (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2023)
Type -2 Diabetes is a disease that is difficult to cure but can be controlled with lifelong medication and a healthy lifestyle. The aim of this study was to determine the effect of the relationship between knowledge of type-2 diabetes patients and patient adherence to taking diabetes medication in Karawang Kulon, West Java. The research method is descriptive correlation where the samples in this study were all type 2 diabetes patients in January 2023-February 2023 with a total of 311. The results showed that the level of knowledge of type -2 diabetes patients was good at 92.60%, and quite good at 7.4%. while the level of compliance is 13.83% compliance, 54.98% sufficient compliance and 31.19% disobedience. The results of the study based on the chi square test obtained a value of 0.00 <0.05, which means that there is a significant relationship between the level of knowledge of type 2 diabetes patients and adherence to taking diabetes medication in Karawang Kulon.